Peter Vale, Lawrence Hamilton and Estelle H. Prinsloo (eds), Intellectual Traditions in South Africa: Ideas, Individuals and Institutions (Historia, 2021)
This volume fills a dearth of scholarship in the under-researched, yet extremely relevant, scholarly space of intellectual histories in South Africa. Neatly organised in three parts, Vale, Hamilton and Prinsloo expertly manoeuvre the reader through theintellectual cross-currents of South Africa’s history by pointing us to instances of agency, discovery, recovery and ultimately of re-imagining, by connecting us with a contentious past and inscribing an equally unstable present. This volume foregroundsmultidisciplinarity in a refreshingly novel and unexpected way as it also engages with South African history. It does so by using numerous disciplinary lenses that transcend the whole spectrum of humanities and social sciences to create an exciting andstimulating read, which simultaneously incites and begs further scholarly exploration. The mix of disciplinary traditions may explain this, but the chapters are not steeped in any disciplinary apparel. In fact, the writers disrupt conventions and normsbecause the chapters are written to satisfy a differentiated audience that comprises methodological purists, theoretical disciples and generalists. This is a major advantage of this collection because it is not only accessible to this differentiatedaudience but also allows them, despite their perceived differences, an opportunity to not only peer into but also engage with each other’s realities.
Keywords: South Africa; Marxism; Afrikaner; African National Congress (ANC); Gandhi; Black Consciousness Movement; religion